2018
DOI: 10.1101/332031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Necroptosis and apoptosis contribute to cisplatin and aminoglycoside ototoxicity

Abstract: 13Ototoxic side effects of cisplatin and aminoglycosides have been extensively studied, but All rights reserved. No reuse allowed without permission.(which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Thus, both necroptosis and apoptosis contributed to alcohol-mediated osteopenia, and necroptosis performed the main inducement. The combination of necroptosis and apoptosis also occurred simultaneously in the process of dexamethasoneinduced MC3T3-E1 cell death [55] and affected the outcomes in liver diseases [56] and other inflammation or tissue damage [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both necroptosis and apoptosis contributed to alcohol-mediated osteopenia, and necroptosis performed the main inducement. The combination of necroptosis and apoptosis also occurred simultaneously in the process of dexamethasoneinduced MC3T3-E1 cell death [55] and affected the outcomes in liver diseases [56] and other inflammation or tissue damage [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [4][5][6] proposed that aminoglycosides might enter hair cells via a mechanoelectrical transducer channel or endocytosis. The exact mechanisms behind the ototoxicity of aminoglycosides remain unclear, but possible mechanisms include oxidative stress, autophagy, caspase-dependent apoptosis, and programmed cell necrosis that depends on receptorinteracting proteins [7]. Previous studies [8,9] suggested that oxidative stress might be the main contributor to aminoglycoside-induced hearing impairment.…”
Section: Introductionmentioning
confidence: 99%